-(5y+2)-(-4y-4)=-4

Simple and best practice solution for -(5y+2)-(-4y-4)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5y+2)-(-4y-4)=-4 equation:


Simplifying
-1(5y + 2) + -1(-4y + -4) = -4

Reorder the terms:
-1(2 + 5y) + -1(-4y + -4) = -4
(2 * -1 + 5y * -1) + -1(-4y + -4) = -4
(-2 + -5y) + -1(-4y + -4) = -4

Reorder the terms:
-2 + -5y + -1(-4 + -4y) = -4
-2 + -5y + (-4 * -1 + -4y * -1) = -4
-2 + -5y + (4 + 4y) = -4

Reorder the terms:
-2 + 4 + -5y + 4y = -4

Combine like terms: -2 + 4 = 2
2 + -5y + 4y = -4

Combine like terms: -5y + 4y = -1y
2 + -1y = -4

Solving
2 + -1y = -4

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -1y = -4 + -2

Combine like terms: 2 + -2 = 0
0 + -1y = -4 + -2
-1y = -4 + -2

Combine like terms: -4 + -2 = -6
-1y = -6

Divide each side by '-1'.
y = 6

Simplifying
y = 6

See similar equations:

| 7x-2=5x-6 | | 2x^2-5+7= | | 75r^2-12=0 | | 4x-20x+25=0 | | (x+1)x-2(x+3)=(2+x)-3x | | 5e+3=-22 | | y=(5x^2-3x+9)-(20x^2+11x-6) | | x=(5x^2-3x+9)-(20x^2+11x-6) | | -5x-2=30 | | x-8.2=-4.3 | | y+22=13 | | 12v+v-13v+v=17 | | 12v+v-13v+v-1=17 | | 7w+3w-w-3w-2w=20 | | k-k+5k=5 | | v-v+2v+2v=12 | | 27c^2+108c-3510=0 | | 3m-m=14 | | 13w-12w=10 | | 66=3x-39 | | 21y^3-33y^2-18y=0 | | x-.1667x=180 | | x-.16x=180 | | x-.2x=80 | | 3p^2+22p-80=0 | | 5n^2-14n-24=0 | | 3-9x=18-4x | | x=100+.2x | | 2x-4x-4x+x-9x= | | 4x+28=36 | | 2b^2-16b-40=0 | | k^2-4k-45=0 |

Equations solver categories